Angiotensin-converting enzyme inhibitors have adverse effects in anti-angiogenesis therapy for hepatocellular carcinoma. (31st March 2021) - Zhang, Su; Cao, Manqing; Hou, Zhenyu; Gu, Xiaoying; Chen, Yongzi; Chen, Lu; Luo, Yi; Chen, Liwei; Liu, Dongming; Zhou, Hongyuan; Zhu, Keyun; Wang, Zhiwei; et al.
Abstract: At present, anti-angiogenic drugs (AADs) are widely used in the systemic treatment of hepatocellular carcinoma (HCC) or other types of cancer, and have achieved good anti-cancer effect, whereas treatment-related proteinuria can affect the routine use of AADs, which in turn abates the overall efficacy. Currently, most clinicians prescribe angiotensin-converting enzyme inhibitors (ACEIs) to alleviate proteinuria according to diabetic nephropathy guidelines or expert recommendations. However, the efficacy of ACEIs in reducing AAD-related proteinuria and its effect on the anticancer effect of AADs is unknown. Our clinical data showed that some HCC patients experienced tumor progression by ACEIs administration for the treatment of proteinuria caused by AADs. Here, we confirmed that in different tumor-bearing mouse models, ACEIs did not delay the appearance of proteinuria or alleviate proteinuria caused by AADs but compromised the anticancer efficacy of AADs. This effect is unrelated to the change in the VEGF signaling pathway. Our data showed that the combination of ACEIs and AADs flared the production of kidney-derived erythropoietin (EPO). In turn, EPO compromises the anti-angiogenic effects of AADs and decreases antitumor activity. In conclusion, for the treatment of proteinuria caused by AADs, ACEIs have no efficacy while also promoting AADs resistance. This finding is of great significance to guide clinical standardized management of side effects of anti-angiogenic therapy for cancer patients. Highlights: ACEIs cannot reduce or delay proteinuria caused by AADs. ACEIs alone do not promote tumor growth of liver cancer subcutaneous tumor. High doses of AADs easily induce stable proteinuria, but the anticancer effect is better. Proteinuria caused by AADs is reversible after withdrawal. ACEIs promotes the production of kidney-derived EPO and reduces the anticancer efficacy of AADs.